PCR-RFLP and Sequencing of trnS/trnfM Fragment of Enhalus acoriodes from Sanur Coastal Waters, Bali, Indonesia: A Preliminary Study - Made Pharmawati; Eka Fibayani Imaniar (Journal of Tropical Life Science, 2016)
This study aimed to evaluate the resolution of PCR-RFLP and sequencing of trnS/trnfM in detecting genetic diversity of seagrass Enhalus acoroides at Sanur Beach, Sindhu Beach and Semawang Beach. This research used six samples E. acoroides from each location. DNA extraction method followed Doyle and Doyle. PCR amplifications were done using primers P672/P673, P674/P675 and ITS4/ITS5 followed by digestion using restriction enzymes EcoRI, PstI, HindIII, BamHI, Rsa, Mva and HinfI. Sequencing analysis used PCR products of primers trnS/trnfM. Testing of DNA sequences of E. acoroides were conducted using BLAST (Basic Local Alignment Search Tool). DNA sequences were further analyzed using MEGA 5.2 software (Molecular Evolutionary Genetic Analysis) to evaluate variations of DNA. The sequence alignments were done using ClustalW software to determine the homology between the DNA sequences. The results showed that 18 samples of E. acoroides from Sanur, Sindhu and Semawang Beach have no polymorphism based on restriction enzyme analyses. Furthermore, sequencing of trnS/trnfM region of 18 samples E. acoroides showed that the sequences were identical. Â Â